A pseudo‐outbreak of Rhinocladiella similis in a bronchoscopy unit of a tertiary care teaching hospital in London, United Kingdom. Issue 4 (24th December 2020) - Abdolrasouli, Alireza; Gibani, Malick M.; de Groot, Theun; Borman, Andrew M.; Hoffman, Peter; Azadian, Berge S.; Mughal, Nabeela; Moore, Luke S.P.; Johnson, Elizabeth M.; Meis, Jacques F.
Abstract: Outbreaks of fungal infections due to emerging and rare species are increasingly reported in healthcare settings. We investigated a pseudo‐outbreak of Rhinocladiella similis in a bronchoscopy unit of a tertiary care teaching hospital in London, UK. We aimed to determine route of healthcare‐associated transmission and prevent additional infections. From July 2018 through February 2019, we detected a pseudo‐outbreak of R. similis isolated from bronchoalveolar lavage (BAL) fluid samples collected from nine patients who had undergone bronchoscopy in a multispecialty teaching hospital, during a period of 8 months. Isolates were identified by MALDI‐TOF mass spectrometry. Antifungal susceptibility testing was performed by EUCAST broth microdilution. To determine genetic relatedness among R. similis isolates, we undertook amplified fragment length polymorphism analysis. To determine the potential source of contamination, an epidemiological investigation was carried out. We reviewed patient records retrospectively and audited steps taken during bronchoscopy as well as the subsequent cleaning and decontamination procedures. Fungal cultures were performed on samples collected from bronchoscopes and automated endoscope washer‐disinfector systems. No patient was found to have an infection due to R. similis either before or after bronchoscopy. One bronchoscope was identified to be used among all affected patients with positive fungal cultures. Physical damage was found in the index bronchoscope; however, no fungus was recovered after sampling of the affected scope or the rinse water of automated endoscope washer‐disinfectors. Use of the scope was halted, and, during the following 12‐month period, Rhinocladiella species were not isolated from any BAL specimen. All pseudo‐outbreak isolates were identified as R. similis with high genetic relatedness (>90% similarity) on ALFP analysis. The study emphasises the emergence of a rare and uncommon black yeast R. similis, with reduced susceptibility to echinocandins, in a bronchoscope‐related pseudo‐outbreak with a potential water‐related reservoir. Our findings highlight the importance of prolonged fungal culture and species‐level identification of melanised yeasts isolated from bronchoscopy samples. Possibility of healthcare‐associated transmission should be considered when R. similis is involved in clinical microbiology samples.